Haemostatic Effects of Supraphysiological Levels of Testosterone in Normal Men - Anderson, R A; Ludlam, C A; Wu, F C W (Thrombosis and Haemostasis, 1995)
The effects of exogenous testosterone on the haemostatic system were studied in a group of 32 healthy men undergoing a clinical trial of hormonal male contraception. The men received 200 mg testosterone oenanthate (TE) weekly i.m., and plasma samples were taken pretreatment, at defined time points up to 52 weeks of treatment, and 4 and 8 weeks after discontinuing TE. This dose of TE caused a 2-fold increase in trough plasma testosterone levels.TE caused a fall in plasma fibrinogen concentration after 16 weeks of treatment. This was sustained for the duration of TE treatment and recovered to pretreatment levels during the recovery phase. There was also a sustained fall in the level of C4b binding protein which showed a rebound to levels above pretreatment during recovery. Levels of antithrombin III and prothrombin fragment F1.2 rose initially during TE treatment, and levels of protein C, protein S (free) and plasminogen activator inhibitor fell, but the concentrations of these factors all returned to pretreatment levels during continued treatment. There was no change in the plasma concentrations of β-thromboglobulin, tissue plasminogen activator, protein S (total), or D-dimer. There was a sustained increase in haemoglobin concentration and haematocrit, without any change in platelet count.The observed changes were consistent with mild activation of the haemostatic system during initial treatment with testosterone. After several months the raised activation markers had returned to pretreatment levels indicating that a new equilibrium had been established which did not appear to be prothrombotic. The increase in prothrombin fragment F1.2 for the first 32 weeks, and at four weeks after discontinuation of treatment, is consistent with prolonged mildly increased prothrombinase activity. The observed substantial fall in fibrinogen is likely to have reduced, whereas the small rise in haemoglobin will have increased, the tendency to arterial thrombosis. We conclude that supraphysiological doses of testosterone do not result in a sustained marked prothrombotic state, but these results do not exclude a small change in thrombotic risk.